2014
DOI: 10.1371/journal.pone.0097469
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive Selection of Reference Genes for Gene Expression Normalization in Sugarcane by Real Time Quantitative RT-PCR

Abstract: The increasingly used real time quantitative reverse transcription-PCR (qRT-PCR) method for gene expression analysis requires one or several reference gene(s) acting as normalization factor(s). In order to facilitate gene expression studies in sugarcane (Saccharum officinarum), a non-model plant with limited genome information, the stability of 13 candidate reference genes was evaluated. The geNorm, NormFinder and deltaCt methods were used for selecting stably expressed internal controls across different tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 51 publications
5
118
1
3
Order By: Relevance
“…Extensive studies on reference gene stability and selection have been reported in various plants for different tissues and development stages, and under diverse stresses [1422]. Traditionally, reference genes such as 18S rRNA , GAPDH (glyceraldehyde-3-phosphate dehydrogenase), ACT (β or γ actin), TUB (α or β tubulin), EF1α (elongation factor 1α), and UBQ (poly-ubiquitin) have been used most frequently as internal control genes [13, 17]. Recently, taking advantage of a variety of databases comprising data from microarrays, expressed sequence tags, and transcriptomes, other stably expressed genes have been used as novel reference genes for qRT-PCR, such as CUL (Cullin), UBCP (ubiquitin carrier protein) [17], CAP (adenylyl cyclase-associated protein), SKIP1 (ASK-interacting protein 1) [22], F-BOX (F-box/kelch-repeat protein) [23], PP2A (protein phosphatase 2A) [24], SAMDC (s-adenosyl methionine decarboxylase) [12, 25], and SNF (sucrose non fermenting-1 protein kinase) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies on reference gene stability and selection have been reported in various plants for different tissues and development stages, and under diverse stresses [1422]. Traditionally, reference genes such as 18S rRNA , GAPDH (glyceraldehyde-3-phosphate dehydrogenase), ACT (β or γ actin), TUB (α or β tubulin), EF1α (elongation factor 1α), and UBQ (poly-ubiquitin) have been used most frequently as internal control genes [13, 17]. Recently, taking advantage of a variety of databases comprising data from microarrays, expressed sequence tags, and transcriptomes, other stably expressed genes have been used as novel reference genes for qRT-PCR, such as CUL (Cullin), UBCP (ubiquitin carrier protein) [17], CAP (adenylyl cyclase-associated protein), SKIP1 (ASK-interacting protein 1) [22], F-BOX (F-box/kelch-repeat protein) [23], PP2A (protein phosphatase 2A) [24], SAMDC (s-adenosyl methionine decarboxylase) [12, 25], and SNF (sucrose non fermenting-1 protein kinase) [26].…”
Section: Introductionmentioning
confidence: 99%
“…More than chance, the usage of the reported suitable reference genes in a different species or an altered condition leads to misleading results. Recently, more candidate reference genes are isolated and identified using gene expression profile data in many plants, including Saccharum (Ling et al, 2014), Elaeis guineensis (Chan et al, 2014), Tectona grandis L.f. (Galeano et al, Gene xxx (2015) xxx-xxx Abbreviations: qRT-PCR, Quantitative real-time PCR; Ct, threshold cycle (previously); Cq, quantification cycle; HKGs, Housekeeping genes; SD, standard deviation; CV, coefficient of variation; 18S, 18s ribosomal RNA; ACT7a, Actin (ACTIN7); ACT7b, Actin (ACTIN7); ADF, Actin depolymerizing factor; ADF4, Actin depolymerizing factor 4; eIF1Aa, Eukaryotic translation initiation factor 1A; eIF1Ab, Eukaryotic translation initiation factor 1A; eIF2, Eukaryotic translation initiation factor; eIF3, Eukaryotic translation initiation factor; FP, F-box family protein; PTP, Trosine phosphatase; RH2a, DEAD box RNA helicase,RH2; RH2b, DEAD box RNA helicase,RH2; ROC3, Cytosolic cyclophilin (ROC3); UBC1, Ubiquitin-protein ligase; UBC2a, Ubiquitin-protein ligase (ATUBC2); UBC2b, Ubiquitin-protein ligase (ATUBC2); UBC3, Ubiquitin-protein ligase; UBC4, Ubiquitin-protein ligase; YLS8, Mitosis protein YLS8.…”
Section: Introductionmentioning
confidence: 99%
“…Three differentially expressed genes of interest, topoisomerase gene (EU048780), ethylene insensitive gene (EU048778), and tetraspanin gene (EU048770), were selected for expression profile analysis. Primers specific to the sugarcane 25S rRNA gene were used for normalization of the reactions (Ling et al, 2014), and real-time qPCR primers were designed using Primer premier 5.0 (Table 2).…”
Section: Real-time Qpcr Confirmation and Expression Profile Analysis mentioning
confidence: 99%